Cyclic vomiting syndrome in a 27‐year‐old male: A case report. Issue 7 (9th July 2021) - Arafat, S.M. Yasir; Mondal, Firoj; Ghimire, Sabina; Perveen, Irin
Abstract: A 27‐year‐old man presented with post‐meal chest tightness followed by vomiting for 3 years. With a multidisciplinary approach, he was labeled as cyclical vomiting syndrome and treated with pharmacotherapy, psychotherapy, and lifestyle modifications. Abstract : A 27‐year‐old man presented with post‐meal chest tightness followed by vomiting for 3 years. With a multidisciplinary approach, he was labeled as cyclical vomiting syndrome and treated with pharmacotherapy, psychotherapy, and lifestyle modifications.